THE ROLE OF INTEGRATION OF PHYSICS AND ENGLISH IN INCREASING EDUCATIONAL EFFICIENCY IN PHYSICS LESSONS - N.Z.Mamadaliyeva (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Annotation.This article explores the pedagogical potential and practical benefits of integrating the English language into physics instruction. It argues that a bilateral approach—teaching physics through English-not only enhances students’ language proficiency but also deepens their understanding of physical concepts. By examining the methodologies for creating a bilingual learning environment, the article demonstrates how this integration fosters critical thinking, improves access to global scientific resources, and better prepares students for international academic and professional collaboration. The study concludes that the synergy between language and science education significantly increases the overall efficiency of the physics lesson, making learning more contextual, engaging, and relevant to modern globalized standards.